Wireless sensor network based monitoring system for precision agriculture in Uzbekistan - Farruh Muzafarov; Abdimurod Eshmuradov (Universitas Ahmad Dahlan, 2019)
The last decades the WSN technology has been adopted by more and more scientific fields for accurate and effective monitoring of climate phenomena like air pollution, destruction phenomena like landslides, etc. It has been widely used in agriculture for field monitoring. WSN is an emerging technology, which through the research in the labs and the real deployments has been proved to be a significant and valuable tool for scientists to explore another world which is behind the various environmental phenomena using tiny sensor nodes In this article,